Addressing McKenzie’s Challenge Regarding Progress in Naturalized Metaphysics (Culturas Científicas, 2025)
In this article, I elaborate a proposal to overcome McKenzie’s argument against the possibility of progress-talk in metaphysics (2020). McKenzie states that said discourse is not possible in metaphysics due to its “all-or-nothing” character: either metaphysical theories are true or not, without intermediaries, so the language of approximation cannot meaningfully apply to changes between metaphysical theories. I show that discussions regarding the type of metaphysical relationship between two relata are susceptible to retention and refinement, two criteria that McKenzie considers necessary for progress, as long as they tend towards better matching what is observable in reality. This is possible if metaphysical relationship types are characterized as sets of properties, from which the Jaccard Index between two sets can be utilised to determine the degree of similarity or approximation between relationship types. If such is the case, then a transition from one relationship thesis to another can be considered progress as long as some properties are retained and the change is guided by empirical evidence. Hence, progress-talk in naturalized metaphysics is possible according to McKenzie’s own criteria.
Keywords: Metametaphysics; Set theory; Jaccard index; Metaphysical relationship; Metaphysics of biology